Harmonisasi Kebijakan Fiskal dan Lingkungan: Tinjauan Yuridis Skema 'Cap and Tax' dalam Pajak Karbon 2026 - Ardini, Difa; Khotimah, Anggun Husnul; Handayani, Sri (Indo Publishing, 2026)
Indonesia's increasing carbon emissions, reaching 674.5 million tons of CO₂e in 2023, and continued dependence on fossil fuels, have prompted an urgent evaluation of the effectiveness of the national carbon tax policy, particularly the cap and tax scheme mandated by the 2021 HPP Law and updated through Presidential Regulation 110/2025 ahead of its full implementation in 2026. This study uses a qualitative approach with a document analysis design of primary regulations, indexed scientific journals, and international agency reports for the 2015–2025 period. The results show that although the regulatory architecture of Indonesia's cap and tax scheme has been designed with sound policy logic, its implementation is hampered by excessively low tariffs (USD 2.02/ton), stagnant carbon market performance (total IDX Carbon transactions were only USD 4.9 million in two years), and four mutually reinforcing structural disharmonies: the absence of a revenue recycling mechanism, the paradox of fossil fuel subsidies, institutional fragmentation across ministries, and very narrow sectoral coverage. These findings confirm that harmonization of fiscal and environmental policies is a prerequisite, not merely a complement, for the effectiveness of carbon pricing instruments in developing countries. Gradual tariff reform, partial earmarking, and readiness-based sectoral expansion are policy agendas that cannot be postponed before 2026.